Voids in the H-bonded network of water and their manifestation in the structure factor - Barker, DR; Wilson, M; Madden, P; Medvedev, N; Geiger, A (American Inst of Physics, 2000)
The main peak of the oxygen-oxygen structure factor SOO(Q) of water shows an unusual doublet structure and the low-Q feature of this doublet shifts appreciably with pressure. This pressure dependence is cited as evidence of polymorphism in water. This feature is analogous to the `prepeak,' or `first-sharp-diffraction peak' which is well known in network-forming ionic liquids.